Effects of coffee husk and cocoa pods biochar on the chemical properties of an acid soil from West Cameroon. Issue 5 (16th April 2023) - Pouangam Ngalani, Gilles; Dzemze Kagho, Frank; Peguy, Nanseu Njiki Charles; Prudent, Pascale; Ondo, Jean Aubin; Ngameni, Emmanuel
ABSTRACT: Evaluation of liming and fertility properties of biochar on acid soil was studied in this work. Selected soil properties such as pH, electrical conductivity (EC), exchangeable acidity (Ex Ac), exchangeable Al (Ex Al), exchangeable Fe (Ex Fe), available P and, soil organic carbon (SOC) were examined under the effect of biochar amendments. The acid soil was treated with biochar issued from coffee husk (CH) and cocoa pods (CP) pyrolyzed at 350°C and 550°C for 4 hours at amendment rate of 0, 20, 40 and 80 g kg −1 and an incubation time of 7, 14, 30, 40 and 60 d. Biochar amendments significantly increased soil pH, soil EC with respect to control and decrease in exchangeable acidity was observed. Results show that biochar improved available P in acid soil, though re-adsorption occurred with increasing incubation time. A significant increase in SOC is observed as compared to control. The impact of biochar on these acid soil chemical properties is due to the properties which are dependent on the biochar type and pyrolysis temperature. Thus, biochar can play the dual role of a liming agent and a source of P fertilizer nutrients.